Epiregulin dysregulation in polycystic ovary syndrome: metabolic and ovarian implications - Zainab Ghazi Mohammed; Hassan Ali Farman (Middle East Fertility Society Journal)
Abstract Background Polycystic ovary syndrome (PCOS) is a multifactorial endocrine disorder characterized by metabolic and reproductive abnormalities. Emerging evidence suggests epidermal growth factor (EGF)–like peptides may be implicated in PCOS pathophysiology, but data on epiregulin remain limited. Objective To evaluate circulating epiregulin levels in women with PCOS and explore its associations with metabolic and reproductive parameters. Methods A case–control study included 60 women with PCOS, diagnosed according to the Rotterdam criteria, and 30 healthy controls, matched for age. Anthropometric measurements (body mass index, blood pressure), fasting insulin and glucose levels, and reproductive hormones (luteinizing hormone (LH), follicle‑stimulating hormone (FSH), testosterone, estradiol, and progesterone) were assessed. Serum epiregulin was measured by ELISA. Statistical comparisons were performed using independent t-tests or Mann–Whitney U tests, and Pearson’s or Spearman’s correlation was used for associations. Results Women with PCOS had significantly higher BMI (p < 0.001), fasting insulin (p < 0.001), and Homeostatic Model Assessment of Insulin Resistance (HOMA‑IR) scores (p < 0.001) compared to controls. LH and testosterone levels were also elevated, while FSH, estradiol, and progesterone were lower in the PCOS group (all p < 0.001). Notably, circulating epiregulin concentrations were significantly higher in PCOS (p < 0.001). Conclusion This study confirms the classic endocrine and metabolic disturbances in PCOS and identifies elevated serum epiregulin as a novel finding. Although correlations with key reproductive hormones were not statistically significant, the potential role of epiregulin in ovarian folliculogenesis warrants further investigation. Enhanced understanding of epiregulin signaling could open new avenues for targeted therapies and improved management of PCOS.